2019
DOI: 10.1107/s1600577518017691
|View full text |Cite
|
Sign up to set email alerts
|

In situ synchrotron research of phase formation in mechanically activated 3Ti + Al powder composition during high-temperature synthesis under the condition of heating with high-frequency electromagnetic fields

Abstract: An in situ synchrotron study of the specific features of the phase formation dynamics in mechanically activated 16 wt% Al + Ti powder composition is described, the high-temperature synthesis being carried out under the condition of high volume inflammation by means of inductive heating. The kinetics of the phase formation were registered with an experimental complex, especially designed, constructed and adjusted for the method of dynamic diffraction analysis in synchrotron radiation beams. It has been experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For a detailed study of in situ phase formation in the synthesis of clad precursors of Ti 64 wt% + Al composition, synchrotron radiation time-resolved diffractometry was applied. It should be noted that similar studies were previously conducted for mechanoactivated samples of the same composition, but without the deposited shell on them; the results are given by Loginova et al (2019a).…”
Section: Results Of the Experimentsmentioning
confidence: 65%
See 2 more Smart Citations
“…For a detailed study of in situ phase formation in the synthesis of clad precursors of Ti 64 wt% + Al composition, synchrotron radiation time-resolved diffractometry was applied. It should be noted that similar studies were previously conducted for mechanoactivated samples of the same composition, but without the deposited shell on them; the results are given by Loginova et al (2019a).…”
Section: Results Of the Experimentsmentioning
confidence: 65%
“…Mechanoactivation pretreatment has also been found to lower the maximum synthesis temperatures by reducing the reaction activation energy (Adeli et al, 2017;Xu et al, 2006). Loginova et al (2019a) considered in detail the phase transformations for mechanoactivated Ti +Al mixture. It was found that the characteristic heating rate is 500 K min À1 , and the ignition temperature is lower than the melting of the fusible component (about T = 555 C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5. We assume that surfacing of mechanocomposites will provide additional possibilities for controlling the reaction of high-temperature synthesis in thermal explosion mode [18][19][20][21][22][23][24]…”
Section: Resultsmentioning
confidence: 99%
“…Centripetal mill acceleration 40 g, activation time 7 min. The choice of mechanical activation modes was determined from previous studies [12,13].…”
Section: Objects and Research Methodsmentioning
confidence: 99%